Comparison of Monotherapy Tamsulosin or Solifenacin alone Versus Combination Therapy Tamsulosin plus Solifenacin in the Management of JJ Stent related Urinary Symptoms - Muhammad Rameez, Muhammad Umar Habib, Jamshed Rahim, Amna Kazi, Jamil Rahim, Malik Zain Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ureteral stents are inserted to relieve the ureteral obstruction, reduce obstructive renal pain, increases the urine flow and to avoid the complications. The insertion of ureteral stent can lead to several stent-related complications that comprise lower urinary tract symptoms and dysuria. These complications can affect the QoL and sometimes can cause emergency department or outpatient early visits. Objective: To compare the efficacy and safety of monotherapy with tamsulosin or solifenacin alone versus their combination in the treatment of JJ stent related symptoms. Study Design: Non-randomized control trial comparative study Place and Duration of Study: Department of Urology, Jinnah Hospital Lahore from 1st December 2022 to 31st May 2023. Methodology: One hundred and sixty eight patients who developed JJ stent related symptoms were enrolled. Patients were selected using consecutive sampling technique and randomly allocated one of the three treatments using lottery method. Group A: 56 patients receiving Tamsulosin 0.4 mg daily; Group B: 56 patients receiving Solifenacin 5mg daily; and Group C: 56 patients receiving Combination of Tamsulosin 0.4 mg and Solifenacin 5 mg. The stent related urinary symptoms of all these patients were evaluated by using USSQ before initiation of therapy and fortnightly till the removal of JJ stent after two months by using USSQ. Results: The mean ages were 35.71±7.622 years of Group A (Tamsulosin), 32.43±8.844 years of Group B (Solifenacin) and 32.71±9.400 years of Group C (Tamsulosin + Solifenacin). Significant results in USSQ score were obtained at baseline, first visit, second visit, third visit and fourth visit (P=0.000). The significant results (P≤0.05) were found between Group A and Group C at first visit, second visit, third visit and fourth visit while insignificant results (>0.05) at baseline. However, between Group B and Group C, significant results were found at baseline and all visits. Conclusion: The combination therapy with Tamsulosin plus Solifenacin is more effective than monotherapy with Tamsulosin or Solifenacin alone for JJ stent related urinary symptoms. Keywords: Comparison, Tamsulosin, Solifenacin, Monotherapy, Combination therapy, JJ stent related urinary symptoms.